Damages awarded by Arbitration Board — Application for certiorari to quash award — Wether board has power to award and assess damages

(untitled) (Département des relations industrielles de l’Université Laval, 1961)
SummaryThe union had the capacity to incur liability for damages and the Board of Arbitrators were within their powers in proceeding to assess and award damages. The arbitrators had the same jurisdiction with respect to damages as they had to hear and dispose of the grievance which had arisen from a breach of the agreement. Moreover, since the union had the legal capacity to enter into a collective agreement, it was fastened with the responsibility that arose from a breach thereof and, therefore, it had the capacity to incur liability for damages.In the matter of an arbitration between Polymer Corporation Ltd. and Oil Chemical and Atomic Workers International Union, Local 16-14 Ontario High Court of Justice, January 23, 1961; McRuer, C J.H.C.